Enhanced nucleotide analysis enables the quantification of deoxynucleotides in plants and algae revealing connections between nucleoside and deoxynucleoside metabolism. Issue 2 (8th December 2020) - Straube, Henryk; Niehaus, Markus; Zwittian, Sarah; Witte, Claus-Peter; Herde, Marco
Abstract: Detecting and quantifying low-abundance (deoxy)ribonucleotides and (deoxy)ribonucleosides in plants remains difficult; this is a major roadblock for the investigation of plant nucleotide (NT) metabolism. Here, we present a method that overcomes this limitation, allowing the detection of all deoxy- and ribonucleotides as well as the corresponding nucleosides from the same plant sample. The method is characterized by high sensitivity and robustness enabling the reproducible detection and absolute quantification of these metabolites even if they are of low abundance. Employing the new method, we analyzed Arabidopsis thaliana null mutants of CYTIDINE DEAMINASE, GUANOSINE DEAMINASE, and NUCLEOSIDE HYDROLASE 1, demonstrating that the deoxyribonucleotide (dNT) metabolism is intricately interwoven with the catabolism of ribonucleosides (rNs). In addition, we discovered a function of rN catabolic enzymes in the degradation of deoxyribonucleosides in vivo. We also determined the concentrations of dNTs in several mono- and dicotyledonous plants, a bryophyte, and three algae, revealing a correlation of GC to AT dNT ratios with genomic GC contents. This suggests a link between the genome and the metabolome previously discussed but not experimentally addressed. Together, these findings demonstrate the potential of this new method to provide insight into plant NT metabolism. Abstract : A new method for the quantification of (deoxy)ribonucleotides and nucleosides enables an in-depth analysis of the nucleotide metabolism in plants.